ISLAMIC PARENTING TRAINING FOR MOTHERS IN FORMING CHILDREN'S CHARACTER BASED ON THE QUR'AN - ummah, Wardatul; Jauhari, Irfan (Journal of Islamic Science Community, 2025)
Strengthening the role of mothers in children's education is very important, especially in forming Islamic characters based on the values ​​of the Qur'an. This community service program aims to provide Islamic parenting training to mothers as an effort to equip them with knowledge and skills in educating children in a Qur'anic manner. Activities are carried out through a participatory approach, in the form of lectures, interactive discussions, and direct practice. Training materials include basic concepts of Islamic parenting, methods of educating children according to the values ​​of the Qur'an, as well as the habituation of worship and noble morals in everyday life. The results of the activities show an increase in mothers' understanding of Islamic parenting patterns, as well as a growing awareness of the importance of their role as the first madrasah for children. This program is expected to become a model of family assistance based on Islamic values ​​that can be applied sustainably in society.